Decoupling between policy and practice through the lens of sensemaking and sensegiving = Zjawisko rozdzielenia między polityką a praktyką działania z perspektywy nadawania i tworzenia sensu - Austen, Agata; Kapias, Michał (Zielona Góra: Faculty of Economics and Management Press)
Any organizations, pursuing their goals, they should take into account others, as they are compelled to a joint coexistence. In order to grow, they need plans and rules of conduct. But not always what was intended is actually implemented. That discrepancy is called decoupling.
Keywords: organizacja; zachowania organizacyjne; rzeczywistość organizacyjna; sens działania; sens tworzenia; koegzystencja; odpowiedzialność; organization; organizational behaviour; organizational reality; sensemaking; sensegiving; coexistence; responsibility